Metformin Use Was Associated With Reduced Risk of Incidental Sjögren's Syndrome in Patients With Type 2 Diabetes: A Population-Based Cohort Study - Wang, Cheng-You; Lai, Jung-Nien; Liu, Chin-Hsiu; Hu, Kai-Chieh; Sheu, Kai-Lun; Wei, James Cheng-Chung (Frontiers in Medicine, 2022)
Abstract Purpose Previous studies have shown that metformin exhibits an anti-inflammatory effect and may decrease the risk of incidental diabetes. But the effect of metformin on incidental Sjögren’s syndrome is unknown. The aim of the study was to examine the association between metformin exposure and Sjögren’s syndrome in diabetic patients. Methods The dataset in this retrospective cohort study was obtained from the National Health Insurance Research Database (2000-2013) in Taiwan. In total, 15,098 type 2 diabetic patients under metformin treatment and an equivalent number without metformin treatment matched for comparison were included. The primary endpoint was the incidence of Sjogren’s syndrome. Univariate and multivariate Cox proportional hazards models were used for data analysis. A subgroup analysis and sensitivity test were also performed. Results The incidence rate of Sjögren’s syndrome in non-metformin controls was 40.83 per 100,000 person-years and 16.82 per 100,000 person-years in metformin users. The adjusted hazard ratio (aHR) in diabetic patients under metformin treatment was 0.46 (95% CI, 0.23 to 0.92). In subgroup analysis, men had a lower risk of developing Sjögren’s syndrome than women (aHR = 0.15, 95% CI = [0.05, 0.41]). After prescribing metformin to type 2 diabetic patients aged 60 years or more, those patients had a lower risk of developing Sjögren’s syndrome (aHR = 0.34, 95% CI = [0.12, 0.96]). Conclusion In this large population-based cohort study, metformin exposure was associated with a reduced risk of developing Sjögren’s syndrome in type 2 diabetic patients.